Knowledge of self-care among type 2 diabetes patients in two states of Nigeria - Jackson IL; Adibe MO; Okonta MJ; Ukwe CV (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Objective: To assess the knowledge of self-care practices, as well as factors responsible for such knowledge among type 2 diabetes patients in two states of Nigeria. Methods: Descriptive, cross sectional survey research design was employed. The study was conducted on type 2 diabetes out-patients attending Endocrinology Clinic at the University of Uyo Teaching Hospital (UUTH) and University of Calabar Teaching Hospital (UCTH) between June 2012 and February 2013. The Diabetes Self-care Knowledge (DSCK-30) was used in evaluating knowledge of self-care practices. Socio-demographic information and respondents' opinion on the possible barrier(s) to knowledge of self-care were also obtained. Data were analysed using Microsoft Excel and SPSS version 14.0. Statistical significance for all analyses was defined as a p value less than 0.05. Results: A total of 303 out of 380 questionnaires distributed were completed and returned (response rate =79.7%). The majority of the study sample (79.5%) had 70% or more overall knowledge level about self-care. Self-care knowledge was associated with level of education (p<0.001), monthly income (p<0.001) and duration of diabetes (p=0.008). Negative attitude to disease condition was the only factor associated with knowledge (chi-square value at one degree of freedom =6.215; p=0.013). Conclusion: Diabetes self-care knowledge was generally high among the population studied. Educational status, monthly income, duration of diabetes and negative attitude to disease condition predicted knowledge level.